Disability, Poverty, and Schooling in Developing Countries : Results from 14 Household Surveys - Filmer, Deon (World Bank, 2012)
Analysis of 14 household surveys from 13 developing countries suggests that 1–2 percent of the population have disabilities. Adults with disabilities typically live in poorer than average households: disability is associated with about a 10 percentage point increase in the probability of falling in the two poorest quintiles. Much of the association appears to reflect lower educational attainment among adults with disabilities. People of ages 6–17 with disabilities do not live in systematically wealthier or poorer households than other people of their age, although in all countries studied they are significantly less likely to start school or to be enrolled at the time of the survey. The order of magnitude of the school participation deficit associated with disability—which is as high as 50 percentage points in 3 of the 13 countries—is often larger than deficits related to other characteristics, such as gender, rural residence, or economic status differentials. The results suggest a worrisome vicious cycle of low schooling attainment and subsequent poverty among people with disabilities in developing countries.